A comparison of suitability models to identify prehistoric agricultural fields in western New Mexico. (February 2017) - Healy, A.; Lippitt, C.D.; Phillips, D.; Lane, M.
Abstract: Suitability models can help identify prime environments for a specific form of agricultural field, ak chin, that is difficult to locate with standard archaeological field methods. Using data from western New Mexico, we applied remote sensing and a geographic information system to develop suitability models based on a small training data sample. Three models, Mahalanobis Typicality, Maximum Entropy, and Multi-Criteria Evaluation Ordered Weighted Average, were used and the resulting suitability estimates were visually compared to known patterns of ak chin agriculture and quantitatively compared using receiver operating characteristic area under the curve. Although archaeological fieldwork is needed to verify these results, receiver operating characteristic validation indicates that Mahalanobis Typicality and Maximum Entropy performed well in identifying the potential location of previously undiscovered prehistoric agricultural fields. Highlights: Potential archaeologists to generate suitability models for identifying ak chin style agricultural fields is proposed. Models rely upon specific environmental variables to identify the most suitable ak chin environments. Empirical suitability models—as opposed to expert models—performed best according to validation methods. Suitability modeling in archaeological research appears to be a useful method for locating potential agricultural fields.